Penerapan Strategi Pemasaran dan Tata Kelola UMKM Ekonomi Pancasila di Kelurahan Karet Tengsin Kecamatan Tanah Abang Jakarta Pusat - Teuku Alexander; Susanto Yogo Purnomo; Glen Fortuna Dela Fortega; Ari Prihatni; M Syachro Hendarto (Jurnal Indonesia Sosial Teknologi, 2022)
The background of this research is that increasingly strong business competition makes Micro, Small Medium Enterprises( MSMEs) actors should have a good marketing strategy to remain competitive with their rivals and there is still a lack of science and understanding in dealing with competition in the digital masa and its benefits for business actors. The Faculty of Economics also Business, Bung Karno University( FEB UBK) plans and facilitates lecturers who wish to carry out community service activities. And this is the basis for FEB Bung Karno University Management Study Program to plan community service activities in each annual work plan. The purpose of community service activities at FEB Bung Karno University is to examine how to apply marketing strategies as the tool to increase small medium businesses to the people of Karet Tengsin Village, Tanah Abang District during a pandemic by using social media to establish good relations and communicate with consumers and increase morale creative entrepreneur and looking for new opportunities that exist.